2019
DOI: 10.1021/acs.est.9b06152
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Particulate Organic Nitrogen and Light Absorption of Humic-Like Substances over Tibetan Plateau Due to Long-Range Transported Biomass Burning Emissions

Abstract: To elucidate the influence of long-range transported biomass burning organic aerosols (BBOA) on the Tibetan Plateau, the molecular compositions and light absorption of HUmic-Like Substances (HULIS), major fractions of brown carbon, were characterized during the premonsoon season. Under the significant influence of biomass burning, HULIS concentrations increased to as high as 26 times of the background levels, accounting for 54% of water-soluble organic carbon (WSOC) and 50% of organic carbon (OC). The light ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 83 publications
(186 reference statements)
11
69
0
Order By: Relevance
“…This indicates a more significant wavelength dependence of biomass burning brown carbon aerosols than any of OOA and HOA. As a matter of fact, OA emitted from primary biomass burning contains the largest part of brown carbon chromophores which strongly absorb light at near-UV wavelengths (Huang et al, 2018;Kumar et al, 2018;Lu et al, 2015;Wang et al, 2019). Moreover, the stronger wavelength dependence obtained for MO-BBOA (compared to LO-BBOA, which can be considered as fresher emissions) is consistent with the features of primary vs. secondary biomass burning OA (or oxidized primary OA) reported by Saleh et al (2014).…”
Section: Sources Of Organic Aerosol At Sirtasupporting
confidence: 78%
“…This indicates a more significant wavelength dependence of biomass burning brown carbon aerosols than any of OOA and HOA. As a matter of fact, OA emitted from primary biomass burning contains the largest part of brown carbon chromophores which strongly absorb light at near-UV wavelengths (Huang et al, 2018;Kumar et al, 2018;Lu et al, 2015;Wang et al, 2019). Moreover, the stronger wavelength dependence obtained for MO-BBOA (compared to LO-BBOA, which can be considered as fresher emissions) is consistent with the features of primary vs. secondary biomass burning OA (or oxidized primary OA) reported by Saleh et al (2014).…”
Section: Sources Of Organic Aerosol At Sirtasupporting
confidence: 78%
“…Hence, there is a strong possibility that, those abundant aged BC particles observed in Period I are originated from the fire smokes in South and Southeast Asia. This deduction is in accordance with the conclusions given by Zheng et al (2017) and Wang et al (2019). Based on their chemistry-related evidence, those abundant aged BC are believed to have an origin of biomass burning.…”
Section: Observational Evidence For the Transport Of Biomass Burning supporting
confidence: 91%
“…In our previous publication, Wang et al (2019) have showed that the light absorption at short wavelength by brown carbon is enhanced because of the transport of BB plumes during Period I. In addition to that research, this study reveals that the light absorption by black carbon, which can strongly absorb light at visible and infrared wavelength, is also strongly enhanced by the transported BB plumes.…”
Section: Strong Enhancement Of the Light Absorption Due To The Transpsupporting
confidence: 72%
“…Aging of aerosols is another possible reason that leads to high OC/EC ratios (Zhang et al., 2019). According to the backward trajectories (Figure ), it was likely to be the influence of aerosols transported from South Asia (Wang et al., 2019).…”
Section: Atmospheric Aerosol Chemical Compositionsmentioning
confidence: 99%